Perlindungan Hukum terhadap Ahli Waris Terkait Sertipikat Hak Milik Pihak Lain Diatas Lahan Tanah Warisan - Kusmianti Indah Sari; Felicitas Sri Marniati; Sirajuddin Sailellah (Pusat Riset dan Inovasi Nasional, 2026)
Legal problems in the land inheritance process often arise when inherited land has been registered in the name of another party. This study aims to examine the procedure for registering inherited land that has been issued a Certificate of Ownership (SHM) on behalf of other parties, as well as the form of legal protection for heirs. The research uses a normative juridical approach with a literature study method based on primary, secondary, and tertiary legal materials. The approaches used include legislative, conceptual, analytical, and case approaches. The analysis of legal materials is carried out through grammatical, systematic interpretation, analogous construction, and legal refinement construction. The results of the study show that the registration of inherited land must be carried out by the entitled heirs, especially for land that has not been certified. Registration is carried out sporadically as a form of registration for the first time. Legal protection for heirs is obtained preventively through the land registration process, and repressively in the event of arbitrary actions from other parties or government agencies. This research emphasizes the importance of legal certainty in the process of registering inherited land and the protection of the rights of heirs so that they are not harmed by the existence of other parties' certificates. This effort is part of the fair and transparent enforcement of agrarian law in Indonesia.